Pola Konsumsi Lemak Jenuh, Lemak Tak Jenuh dan Serat pada Penderita Penyakit Jantung Koroner di RSUD Sungai Dareh - Hasneli Hasneli; Yosi Irene Putri; Yolla Hesa Putri; Kasmiyetti Kasmiyetti; Safyanti Safyanti (Poltekkes Kemenkes Padang, 2024)
Coronary heart disease is caused by plaque that accumulates in the coronary arteries, thereby disrupting blood flow to the heart due to consumption of food that is not balanced between intake of saturated and unsaturated fats and fiber. This study aims to determine the picture of saturated fat, unsaturated fat and fiber intake in people with coronary heart disease. This research is descriptive with a cross sectional study design. This research was conducted at Sungai Dareh Regional Hospital in August 2021-June 2022 with a sample size of 38 people. Sampling was carried out using purposive sampling. Research results: 65.8% of respondents had a high saturated fat intake, an average of 12.16%, with bad food consumption habits, the highest frequency was often > 2x/week, 89.5% of respondents had a low unsaturated fat intake. , an average of 5.64%, with the type of food habits that are not good, the highest frequency is rarely ≤ 1×/week, and almost all (94.7%) respondents have less fiber intake with an average of 16.1, with the type food consumption habits are not good, the highest frequency is rarely ≤ 1×/day. Conclusion: Coronary heart disease sufferers at Sungai Dareh Regional Hospital show unhealthy eating patterns with high intake of saturated fat and low intake of unsaturated fat and fiber. It is recommended that the public, especially CHD sufferers, reduce their consumption of saturated fats from foods that contain lots of palm oil and coconut milk and increase their consumption of foods that are sources of unsaturated fats from nuts and vegetable protein.